2005
DOI: 10.1126/science.1107765
|View full text |Cite
|
Sign up to set email alerts
|

U-Pb Ages from the Neoproterozoic Doushantuo Formation, China

Abstract: U-Pb zircon dates from volcanic ash beds within the Doushantuo Formation (China) indicate that its deposition occurred between 635 and 551 million years ago. The base records termination of the global-scale Marinoan glaciation and is coeval with similar dated rocks from Namibia, indicating synchronous deglaciation. Carbon isotopic and sequence-stratigraphic data imply that the spectacular animal fossils of the Doushantuo Formation are for the most part younger than 580 million years old. The uppermost Doushant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
683
4
16

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,171 publications
(730 citation statements)
references
References 30 publications
27
683
4
16
Order By: Relevance
“…The smooth and consistent variation in  13 C values throughout the sampled sections parallels  13 C variations of contemporaneous terminal Neoproterozoic sections (Ries et al, 2010) from China (Condon et al, 2005;Jiang et al, 2003), Australia (Calver, 2000; Page 30 of 74…”
Section: Carbon Isotopesmentioning
confidence: 99%
“…The smooth and consistent variation in  13 C values throughout the sampled sections parallels  13 C variations of contemporaneous terminal Neoproterozoic sections (Ries et al, 2010) from China (Condon et al, 2005;Jiang et al, 2003), Australia (Calver, 2000; Page 30 of 74…”
Section: Carbon Isotopesmentioning
confidence: 99%
“…Likewise, the basal, globally correlated cap carbonate to the Marinoan glaciation, which defines the Cryogenian-Ediacaran boundary, is well-constrained to ca. 635 Ma based on radiometric ages in China (Condon et al, 2005;Zhang et al, 2008), Namibia (Hoffmann et al, 2004), Tasmania (Calver et al, 2013) and NW Canada (Re-Os date; Rooney et al, 2015). Both early and late Cryogenian glaciations, referred to as the Sturtian and Marinoan (based on locations in South Australia), respectively, appear to be globally distributed (Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The Doushantuo cap carbonate succession displays a distinct suite of sedimentary structures and textures including cemented breccias, sheet cracks, tepee-shaped structures, stromatactis-like cavities, peloids, and local barite fans, and negative carbon isotope excursion of about −5‰ (Jiang et al, 2003a(Jiang et al, , 2006Lin et al, 2011;Peng et al, 2011), similar to those observed in equivalent cap carbonates worldwide (Kennedy, 1996;Hoffman et al, 1998;James et al, 2001;Frimmel and Folling, 2004;Shields et al, 2007b;Shen et al, 2008). Additionally, U-Pb Zircon dates indicate that the cap carbonates were deposited at 635 Ma (Condon et al, 2005).…”
Section: Geological Settingmentioning
confidence: 66%
“…B: A conceptual transect (a-a′ in A; not to scale) across the Yangtze block showing the stratigraphic occurrence of the Doushantuo cap carbonates (Jiang et al, 2003a, b). Age data are from Condon et al (2005) and Zhang et al (2008). C: Simplified geological map of the Yangtze Gorges area (Zhao et al, 1985).…”
Section: Geological Settingmentioning
confidence: 99%